Flow cytometry and its applications - PAPADOGIANNAKIS (E. Ι. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ), E. I.; KONTOS (Β. Ι. ΚΟΝΤΟΣ), V. I.; TAMAMIDOU (Μ. ΤΑΜΑΜΙΔΟΥ), M.; ROUMELIOTOU (Α. ΡΟΥΜΕΛΙΩΤΟΥ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Flow cytometry is an automated, multiparametric and quantitative method that counts and analyses the scattering and fluorescence signals produced as a single cell stream passes through a laser beam. This article describes the method along with fluorochromes used and cell labeling techniques. Additionally, details regarding the applications of flow cytometry are also given. Although flow cytometry is not widely used in veterinary science so far, its application in the near future will rise, since more necessary reagents for veterinary use will be in the market.